Peran Gembala Sidang Dalam Konseling Remaja - Priska Manullang (Jurnal Euangelion, 2022)
Abstract: This research is about the application of counseling in adolescents. The title of the study is the role of the pastor in youth counseling. The method used in this study is a qualitative method, which is a description of the description obtained from various sources. The results of this study indicate that the general counseling knowledge possessed by the pastor will be more effective if it is adjusted to the biblical concept. The role of the pastor in youth counseling is to facilitate adolescent counseling activities and act as a counselor. The application of the role of the Pastor in youth counseling is to become a professional companion to direct the identity of the youth, to become a more experienced figure who broadens the youth's horizons, with concern, to become a spiritual father or spiritual parent of the youth and to become a motivator for the youth. So the role of the Pastor in adolescent counseling is needed so that the problems faced by teenagers can be handled properly so that they are in a positive situation and so that troubled teenagers do not vent their problems to other people and their environment so that they are not in a negative situation.  Abstrak: Penelitian ini tentang penerapan konseling di kalangan remaja. Judul Penetian ini adalah Peran Gembala Sidang Dalam Konseling Remaja. Metode yang dipergunakan dalam penelitian ini adalah metode kualitatif yaitu merupakan deskripsi uraian yang didapat dari berbagai sumber. Hasil pembahasan penelitian ini menyatakan bahwa Pengetahuan konseling secara umum yang dimiliki oleh Gembala sidang akan lebih efektif lagi jika disesuaikan dengan konsep Alkitab, Peran Gembala Sidang dalam konseling remaja ialah memfasilitasi kegiatan konseling Remaja dan berperan sebagai Konselor. Penerapan peran Gembala Sidang dalam konseling remaja ialah menjadi pendamping yang profesional untuk mengarahkan jati diri para remaja, menjadi figur yang lebih berpengalaman yang menambah wawasan remaja, dengan kepedulian, menjadi bapak rohani atau orang tua rohani para remaja dan menjadi motivator para remaja. Jadi peran Gembala Sidang dalam kegiatan konseling remaja dibutuhkan supaya masalah yang dihadapi para remaja dapat ditangani dengan baik sehingga berada dalam situasi yang positif dan supaya para remaja yang bermasalah tidak melampiaskan masalahnya kepada orang lain dan lingkungannya sehingga tidak berada dalam situasi negatif.